1979
DOI: 10.1002/ana.410050412
|View full text |Cite
|
Sign up to set email alerts
|

Central somatosensory conduction time in comatose patients

Abstract: Somatosensory conduction time between the dorsal column nuclei and the cerebral cortex may be measured following median nerve stimulation by recording evoked potentials from both scalp and neck. Central conduction times were significantly increased relative to normal (5.6 +/ 0.5 msec) in 11 of 24 comatose patients. Results within 10 and 35 days of onset of coma were correlated with the final clinical outcome. Conduction times were independent of serum phenobarbital (0 to 630 mumol per liter) and of central bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

1984
1984
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(20 citation statements)
references
References 19 publications
2
15
0
3
Order By: Relevance
“…In contrast to the N20 component of the SEP, which is rather resistant to state parameters such as waking and sleep [Lü ders et al, 1986], or barbiturate-induced coma [Hume et al, 1979], the high frequency oscillations superimposing the N20 component of the SEP show a strong state dependency and disappear during sleep [Emerson et al, 1988;Yamada et al, 1988;Hashimoto et al, 1996]. In humans, Antognini et al [1997] have shown, that isoflurane anaesthesia blunts the fMRI response to noxious and innocuous stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the N20 component of the SEP, which is rather resistant to state parameters such as waking and sleep [Lü ders et al, 1986], or barbiturate-induced coma [Hume et al, 1979], the high frequency oscillations superimposing the N20 component of the SEP show a strong state dependency and disappear during sleep [Emerson et al, 1988;Yamada et al, 1988;Hashimoto et al, 1996]. In humans, Antognini et al [1997] have shown, that isoflurane anaesthesia blunts the fMRI response to noxious and innocuous stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…17 N13-N20 IPLs were measured to evaluate the central conduction time. 18 Peaks after N20 were generated after entering the primary sensory cortex. N20-N65 IPLs were measured for cortical responses.…”
Section: Subjectsmentioning
confidence: 99%
“…1973;Ommaya and Gennarelli, 1974). More recently, evoked piitentials have been used to study the later stages of head injuries, and in some of these Shaw, 1979: Hume andCant. 1981) evidence of delayed transmission of somatosensory information to the primary sensory cortex has been found.…”
Section: Introductionmentioning
confidence: 99%